Opportunistic, Parasitic, Strategic, Symbiotic: Entrepreneurship and the Business of Sport. Issue 7 (24th May 2018) - Porter, Dilwyn
Abstract: Stephen Hardy's tripartite sports product (1986), as subsequently refined by George Sage (2004) and recently reconfigured by Wray Vamplew (2018), remains the starting point for any study of entrepreneurship in and around sport. Recent work in business history, especially Daniel Wadhwani and Christina Lubinski's advocacy of 'new entrepreneurial history' (2017), also has implications for sports historians. These perspectives are crucial for identifying and exploring some key characteristics of entrepreneurship, here defined as an essentially creative process during which opportunities are enacted and developed rather than discovered and exploited. Emphasis is placed on innovation and on how new combinations are effected. A provisional taxonomy of new combinations is developed and three principal categories – parasitic, strategic, and symbiotic – are suggested, each relating to the tripartite sports product in a different way. These abstract formulations are illustrated by examples drawn mainly form the business history of late-nineteenth and early twentieth-century sport.